2014
DOI: 10.1021/jm500901e
|View full text |Cite
|
Sign up to set email alerts
|

Pyrano-isochromanones as IL-6 Inhibitors: Synthesis, in Vitro and in Vivo Antiarthritic Activity

Abstract: Bergenin (1), a unique fused C-glycoside isolated from Bergenia species, possesses interesting anti-inflammatory and antipain activities. To study SAR of this scaffold, first-generation derivatives were synthesized and evaluated for inhibition of lymphocyte proliferation and production of pro-inflammatory cytokines. The C-7 substituted derivatives showed inhibition of IL-6 as well as TNF-α production. Bergenin and its most potent IL-6 inhibitor derivatives 4e and 4f were then investigated in a panel of in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…However, pharmacokinetic data of bergenin in mice are not reported, and the plasma concentrations obtained with the highest dose of bergenin administered (50 mg/kg) are thus not known. Therefore, concentrations of bergenin used in vitro experiments were according to references ( Jain et al, 2014 ; Yang et al, 2017 ), and 3, 10, 30 μM were selected. Results showed that bergenin (10, 30 μM) obviously inhibited the expressions of IL-6 and TNF-α in LPS-stimulated peritoneal macrophages and RAW267.4 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pharmacokinetic data of bergenin in mice are not reported, and the plasma concentrations obtained with the highest dose of bergenin administered (50 mg/kg) are thus not known. Therefore, concentrations of bergenin used in vitro experiments were according to references ( Jain et al, 2014 ; Yang et al, 2017 ), and 3, 10, 30 μM were selected. Results showed that bergenin (10, 30 μM) obviously inhibited the expressions of IL-6 and TNF-α in LPS-stimulated peritoneal macrophages and RAW267.4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bergenin is the major bioactive ingredient in the herb drug. It could inhibit collagen-induced arthritis in mice by reducing serum levels of IL-2, TNF-α and IL-6, and down-regulate lipopolysaccharide (LPS)-induced activation of THP-1 cells by decreasing levels of NF-κB and IKKβ ( Jain et al, 2014 ). In addition, bergenin prevented the production of Th1 cytokines (IL-2, IFN-γ and TNF-α) while up-regulated Th2 cytokines (IL-4 and IL-5) in the peripheral blood of mice with adjuvant-induced arthritis ( Nazir et al, 2007 ); bergenin reduced the expressions of NO, TNF-α, IL-1β and IL-6 in mammary glands of mice with LPS-induced mastitis by inhibiting the activation of NF-κB and MAPKs signaling pathways ( Gao et al, 2015 ); bergenin had a therapeutic effect on LPS-induced acute lung injury by inhibiting NF-κB activation ( Yang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bergenin is the C-glucoside of 4- O -methyl gallic acid and can be found in several medicinal plants, including Bergenia crassifolia and Corylopsis spicata ( Liang et al, 2017 ). Bergenin has been reported to have multiple biological activities, including antiarthritic ( Jain et al, 2014 ; Singh et al, 2017 ), immunomodulatory ( Wang et al, 2017 ; Kumar et al, 2019 ), antidiabetic ( Veerapur et al, 2012 ), osteogenic ( Hou et al, 2019 ), neuroprotective ( Barai et al, 2019 ; Ji et al, 2019 ), and wound-healing effects ( Mukherjee et al, 2013 ). Wang et al (2017) showed that bergenin attenuated colitis by activating the peroxisome proliferator-activated receptor (PPAR) γ.…”
Section: Introductionmentioning
confidence: 99%
“…Manohar et al, enzymatically synthesized bakuchiol glycosides to increase the water solubility and reported their antioxidant and ACE inhibitory activities . The synthesis of Mannich derivatives of natural products has been of enormous interest for the production of leads with potent biological activities including anticancer,, antibacterial, anti‐inflammatory,, anti‐oxidant, antifungal and anticonvulsant . Mannich bases impart hydrophillicity by incorporation of nitrogen atom, hence increasing the bioavailability which in turn improves the efficacy against tumors ,.…”
Section: Introductionmentioning
confidence: 99%